2020
DOI: 10.32737/2221-8688-2020-1-33-39
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aluminum Hydroxide Concentration on Properties and Crystallization Regularities of Composite Materials Based on High and Low Density Polyethylene Mixtures

Abstract: The article presents results of research into the influence of aluminum hydroxide concentration on properties and crystallization regularities of composite materials based on mixtures of high and low density polyethylene. Studies were carried out with samples containing 1, 3, 5 and 10 % wt. aluminum hydroxide. All composite materials were based on mixtures of high and low density polyethylene, taken in 50/50 ratio. Dilatometric studies were carried out on an IIRT-1 device in the course of stepwise cooling of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Nevertheless, for the solid state region, it can be said that the values of the "free" specific volume of the composites at room temperature are practically equal. However, previous studies have shown [17] that with an increase in the amount of aluminum hydroxide in composites based on a polyethylene mixture, the values of the "free" specific volume increase, which contributes to the loosening of the material and thereby the deterioration of the physicalmechanical properties. Most likely, the modifi-cation of the polymer mixture with a structureforming agent contributes to the uniform distribution of the filler in the volume of the polymer matrix and to the enhancement of interaction at the phase boundary, which leads to equalization of the values of the free specific volume of the composites at room temperature.…”
Section: Results and Discussmentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, for the solid state region, it can be said that the values of the "free" specific volume of the composites at room temperature are practically equal. However, previous studies have shown [17] that with an increase in the amount of aluminum hydroxide in composites based on a polyethylene mixture, the values of the "free" specific volume increase, which contributes to the loosening of the material and thereby the deterioration of the physicalmechanical properties. Most likely, the modifi-cation of the polymer mixture with a structureforming agent contributes to the uniform distribution of the filler in the volume of the polymer matrix and to the enhancement of interaction at the phase boundary, which leads to equalization of the values of the free specific volume of the composites at room temperature.…”
Section: Results and Discussmentioning
confidence: 96%
“…According to the given dilatometric curves, the temperature of the onset of crystallization or the first-order phase transition of the modified composites based on aluminum hydroxide and a mixture of polyethylenes practically does not change and is equal to 105 0 C. It has been established that the interactions between the structure-forming agent particles and the polymer components are the decisive factors for the redistribution and agglomeration of aluminum hydroxide particles. Previously, in [17], it was shown that, in the absence of a structureforming agent, the concentration of aluminum hydroxide affects the composites crystallization onset temperature in a mixture of high and low density polyethylene, which is expressed in the mixing of the first-order phase transition temperature. It is known that the process of melt crystallization occurs in three stages [18]: 1) primary nucleation, 2) secondary nucleation leading to crystal growth, and 3) secondary crystallization.…”
Section: Results and Discussmentioning
confidence: 99%
“…The results obtained for the specific gravity show a significant difference between recycled and non-recycled HDPE. The changes in crystalinity structure, porosity and loss of plasticizers during the remelting process while recycling are possible reasons for the change in specific gravity (Mustafayeva, 2020). Generally, the greater the proportion of crystalline regions, the higher the density of the material.…”
Section: Specific Gravitymentioning
confidence: 99%